Obesity development in adults and children as a effect of psychosomatic factors - Aleksandra Kułakowska; Agnieszka Siedlak; Bartłomiej Lepczyński; Philip Kłakowicz; Sebastian Lechowski (Kazimierz Wielki University, 2023)
The aim of this chapter is to explain how psychosomatic factors influence the development of obesity in children and adults. Obesity is one of the most popular chronic diseases, and it puts a person at risk for heart disease. Obesity promotes worry, stress, and depression, as well as affecting self-esteem and acceptance, according to scientific evidence. Obesity is becoming more common among children, which has been linked to bullying and emotional deterioration. As a result, in addition to seeing a dietician, an obese person should seek psychological help.